Pengembangan Job Safety Analysis untuk Workshop Praktik Plumbing di Pendidikan Vokasional Konstruksi Bangunan Universitas Negeri Jakarta - Amanda Lia Saraswati; Tuti Iriani; Santoso Sri Handoyo (LPPM Universitas Negeri Jakarta, 2019)
Abstract This study aims to develop Job Safety Analysis for plumbing practice workshop in Vocational Education of Building Construction as an effort to improve Health and Safety Management System. This research was conducted in Vocational Education Study Program of Building Construction of Faculty of Engineering, State University of Jakarta Building L Campus A UNJ, Jalan Rawamangun Muka, Jakarta 13220. The research time was conducted for 5 months ie in March 2018 s / d July 2018 consisting of three stages: preparation stage, implementation phase and data processing stage. The type of research used in this study using Research & Development methodology.The results showed that: Job Safety Analysis Development for plumbing practice workshop Vocational Education of Building Construction can already be implemented, based on validation results conducted by experts of Job Safety Analysis. Keywords: Development, Job Safety Analysis, Plumbing.